Reorganizing a hospital ward as an accountable care unit. Issue 1 (17th November 2014) - Stein, Jason; Payne, Christina; Methvin, Amanda; Bonsall, Joanna M.; Chadwick, Liam; Clark, Diaz; Castle, Bryan W.; Tong, David; Dressler, Daniel D.
<x xml:space="preserve">Abstract</x> Traditional hospital wards are not specifically designed as effective clinical microsystems. The feasibility and sustainability of doing so are unclear, as are the possible outcomes. To reorganize a traditional hospital ward with the traits of an effective clinical microsystem, we designed it to have 4 specific features: (1) unit‐based teams, (2) structured interdisciplinary bedside rounds, (3) unit‐level performance reporting, and (4) unit‐level nurse and physician coleadership. We called this type of unit an accountable care unit (ACU). In this narrative article, we describe our experience implementing each feature of the ACU. Our aim was to introduce a progressive approach to hospital care and training. Journal of Hospital Medicine 2015;10:36–40. © 2014 Society of Hospital Medicine